2003
DOI: 10.1021/ma0213448
|View full text |Cite
|
Sign up to set email alerts
|

Layered Silicate Nanocomposites Based on Various High-Functionality Epoxy Resins:  The Influence of Cure Temperature on Morphology, Mechanical Properties, and Free Volume

Abstract: This paper investigates the relationship between cure temperature, morphology, and mechanical properties of di-, tri-, and tetrafunctional high-performance, epoxy layered-silicate nanocomposites. Wide-angle X-ray analysis (XRD) was carried out at different stages of cure to monitor organoclay exfoliation kinetics. It was found that some (small) degree of conversion was required to obtain significant intercalation. The nanocomposite morphology was also probed using transmission electron microscopy, XRD, and pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
132
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 206 publications
(143 citation statements)
references
References 33 publications
10
132
1
Order By: Relevance
“…It transpires that the first reaction, which takes place within the clay galleries and promotes the exfoliation of the clay, is enhanced at higher cure temperature, and hence higher isothermal cure temperatures give rise to increased exfoliation in the cured nanocomposite. This result is in agreement with the observations of Becker et al [21], who concluded that higher cure temperatures were found to improve clay delamination, as well as increasing the toughness and modulus in the case of both DGEBA-and TGAP-based materials. In order to further clarify the process of exfoliation in these TGAP-based systems, the goal of the present paper is to investigate the non-isothermal (dynamic) cure behaviour of the same system for comparison with the isothermal cure behaviour, to obtain the kinetic parameters and activation energy, and to analyse the quality of the final nanostructure.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…It transpires that the first reaction, which takes place within the clay galleries and promotes the exfoliation of the clay, is enhanced at higher cure temperature, and hence higher isothermal cure temperatures give rise to increased exfoliation in the cured nanocomposite. This result is in agreement with the observations of Becker et al [21], who concluded that higher cure temperatures were found to improve clay delamination, as well as increasing the toughness and modulus in the case of both DGEBA-and TGAP-based materials. In order to further clarify the process of exfoliation in these TGAP-based systems, the goal of the present paper is to investigate the non-isothermal (dynamic) cure behaviour of the same system for comparison with the isothermal cure behaviour, to obtain the kinetic parameters and activation energy, and to analyse the quality of the final nanostructure.…”
Section: Introductionsupporting
confidence: 93%
“…Most of the studies of the cure reaction of epoxy PLS nanocomposites have concentrated on the iso -thermal or non-isothermal cure of bi-functional epoxy resin systems, typically diglycidyl ether of bisphenol-A (DGEBA); for example, only reference 13 of those cited immediately above (references 8 to 20) does not use DGEBA. Considerably less attention has been paid to the isothermal and/or non-isothermal cure behaviour of PLS nanocomposites based upon high-functionality epoxy resins, though there are exceptions, such as the study of triand tetra-functional epoxy resin systems [21] and our own earlier investigations of a tri-functional epoxy resin nanocomposite system based upon triglycidyl p-amino phenol (TGAP) [22,23]. Strangely, Becker et al [21] found that the DGEBA resin resulted in better exfoliation than for the resins of higher functionality, which is exactly contrary to our own experience.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A similar structure has been observed in layered block copolymer-silicate nanocomposites. [32][33][34] The diameter of the rod-like structures was relatively consistent at 30 nm. The PEO-PE block copolymer has a low molecular weight, M nPEO-PE ¼ 1400 g/mol, with an estimated end-to-end distance of 156 Å , based on exclusion volume and monomer unit lengths given by Almdal et al 35 Thus, the rodlike structures were not simply produced by extended PEO blocks at the outer shell and the PE blocks in the core; a more complex structure must have formed.…”
Section: Resultsmentioning
confidence: 94%
“…In tandem, a range of different mixing procedures, including ultrasonic mixing and high shear mixing, have been used to produce epoxy / clay nanocomposites [3]. Most of these efforts at nanocomposite formation utilize solvents [4] and / or high temperature processing [5] to obtain clay dispersion in the epoxy-amine matrix.…”
Section: Introductionmentioning
confidence: 99%